2020
DOI: 10.3390/ijerph17249223
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Health Disparities in the Rural United States: Advocacy as Caregiving among Community Health Workers and Promotores de Salud

Abstract: Rural populations in the United States are faced with a variety of health disparities that complicate access to care. Community health workers (CHWs) and their Spanish-speaking counterparts, promotores de salud, are well-equipped to address rural health access issues, provide education, and ultimately assuage these disparities. In this article, we compare community health workers in the states of Indiana and Texas, based on the results of two separate research studies, in order to (1) investigate the unique ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 47 publications
2
31
0
5
Order By: Relevance
“…Healthcare systems and hospitals have engaged community health workers, who are trusted members of local communities with shared lived experience, to bridge medical distrust among racial/ethnic minority individuals. Community health workers have been instrumental in providing reliable health information, combatting misinformation, and helping racial/ethnic minority individuals navigate the healthcare system and social support resources [ 4 , 5 ]. Moreover, while COVID-19 infections were initially concentrated in urban areas, which typically had larger racial/ethnic minority populations, the pandemic is now widespread in the United States [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare systems and hospitals have engaged community health workers, who are trusted members of local communities with shared lived experience, to bridge medical distrust among racial/ethnic minority individuals. Community health workers have been instrumental in providing reliable health information, combatting misinformation, and helping racial/ethnic minority individuals navigate the healthcare system and social support resources [ 4 , 5 ]. Moreover, while COVID-19 infections were initially concentrated in urban areas, which typically had larger racial/ethnic minority populations, the pandemic is now widespread in the United States [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, an important consideration in future research is how geographic location may affect the stressors, strategies, or user needs amid the pandemic. Research has shown that there are differences in health workers’ qualifications in urban versus rural areas [ 43 ]. These differentials directly impact the level of knowledge and willingness to work during crisis situations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To serve as functional health diplomats who advocate to address health disparities, VHWs should be able to perform social and medical roles, such as mobilising local populations to receive antenatal care, vaccination, or malaria treatment [ 7 ]. Indeed, VHWs’ advocacy should be viewed as a form of caregiving within the existing primary health care [ 35 ]. To fulfil this multifaceted role, VHWs must be equipped with adequate tools [ 17 ], which in our case were malaria diagnostic and treatment tools.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is a lack of attention concerning lay health workers’ political role and status that may shape their social and medical roles. Only in the American context lay health workers have been described as social justice and policy advocates in addition to their role as health promoters and social agents [ 32 35 ]. In this instance, lay health workers who previously had leadership or advocacy training were likely to advocate at the political and civic level [ 32 , 33 ] and inform policies based on communities’ realities [ 34 ] as a ‘broker’ between the poor (in community) and the state [ 14 ].…”
Section: Introductionmentioning
confidence: 99%